Rescue of cell death and inflammation of a mouse model of complex 1-mediated vision loss by repurposed drug molecules - Yu, Alfred K (Hum Mol Genet, 2017)
Inherited mitochondrial optic neuropathies, such as Leber’s hereditary optic neuropathy (LHON) and Autosomal dominant optic atrophy (ADOA) are caused by mutant mitochondrial proteins that lead to defects in mitochondrial complex 1-driven ATP synthesis, and cause specific retinal ganglion cell (RGC) loss. Complex 1 defects also occur in patients with primary open angle glaucoma (POAG), in which there is specific RGC loss. The treatment of mitochondrial optic neuropathy in the US is only supportive. The Ndufs4 knockout (Ndufs4 KO) mouse is a mitochondrial complex 1-deficient model that leads to RGC loss and rapid vision loss and allows for streamlined testing of potential therapeutics. Preceding RGC loss in the Ndufs4 KO is the loss of starburst amacrine cells, which may be an important target in the mechanism of complex 1-deficient vision loss. Papaverine and zolpidem were recently shown to be protective of bioenergetic loss in cell models of optic neuropathy. Treatment of Ndufs4 KO mice with papaverine, zolpidem, and rapamycin-suppressed inflammation, prevented cell death, and protected from vision loss. Thus, in the Ndufs4 KO mouse model of mitochondrial optic neuropathy, papaverine and zolpidem provided significant protection from multiple pathophysiological features, and as approved drugs in wide human use could be considered for the novel indication of human optic neuropathy.